Effect of bright light therapy combined with five-element music therapy on negative emotions and sleep quality of pregnant women (强光联合五音疗法对孕妇负面情绪及睡眠质量的影响) - ZHANG Caixia (张彩霞); ZHANG Ping (张萍); CAI Donglin (蔡东林); AN Rongrong (安溶溶) (中西医结合护理)
Objective To explore the effect of bright light therapy combined with five-element music therapy on negative emotions and sleep quality of pregnant women with depression. Methods Totally 70 cases of depressed pregnant women were selected and randomly divided into control group and study group, with 35 cases each. Patients in the two groups were given routine nursing programs, and the study group was given bright light therapy combined with five-element music therapy. The Self-rating Anxiety Scale(SAS) score, Self-rating Depression Scale (SDS) score, Pittsburgh Sleep Quality Index (PSQI) score and nursing quality indexes were compared between two groups. Results After intervention, except for the SDS score of the control group, the SAS, SDS and PSQI scores of the two groups were lower than before, and the differences were statistically significant (P<0. 01). The SAS, SDS and PSQI of the study group were lower than those of the control group (P<0. 01), and the scores of each item of nursing quality were higher than those of the control group, with significant differences(P<0. 01). Conclusion Bright light therapy combined with five-element music therapy can relieve the negative emotions and improve the sleep quality of pregnant women with depression. (目的 探讨强光联合五音疗法对孕妇负面情绪及睡眠质量的影响。方法 选择2019年1月—12月于苏州高新区人民医院就诊的抑郁孕妇70例, 按随机数字表法分为对照组和研究组, 各35例。2组孕妇均给予常规护理方案, 研究组增加强光联合五音疗法干预。比较2组产妇干预前后焦虑自评量表(SAS)、抑郁自评量表(SDS)、匹兹堡睡眠质量指数(PSQI)和护理质量指标。结果 干预后, 除对照组SDS评分外, 2组SAS、SDS和PSQI评分均较干预前降低, 差异有统计学意义(P<0. 01)。干预后研究组患者SAS、SDS和PSQI均低于对照组, 差异有统计学意义(P<0. 01)。研究组护理质量各项目评分均高于对照组, 差异有统计学意义(P<0. 01)。结论 强光联合五音疗法可改善孕妇的负面情绪和睡眠质量, 提高护理质量。)